2014
DOI: 10.4103/2141-9248.129022
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge of first aid skills among students of a medical college in Mangalore city of South India

Abstract: Background:The adequate knowledge required for handling an emergency without hospital setting at the site of the accident or emergency may not be sufficient as most medical schools do not have formal first aid training in the teaching curriculum.Aim:The aim of this study is to assess the level of knowledge of medical students in providing first aid care.Subjects and Methods:This cross-sectional study was conducted during May 2011 among 152 medical students. Data was collected using a self-administered question… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
36
3
5

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(51 citation statements)
references
References 15 publications
(21 reference statements)
7
36
3
5
Order By: Relevance
“…Half of the respondents demonstrated fair/moderate knowledge regarding burn first aid. This is similar to that reported in studies on medical students elsewhere 11,12 , though the mean scores achieved in our study is higher than that by medical students in Pakistan 5,11 . Similar conclusions were made regarding nurse's knowledge on burns as being poor, irrespective of their field of specialization in a study 13 .…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Half of the respondents demonstrated fair/moderate knowledge regarding burn first aid. This is similar to that reported in studies on medical students elsewhere 11,12 , though the mean scores achieved in our study is higher than that by medical students in Pakistan 5,11 . Similar conclusions were made regarding nurse's knowledge on burns as being poor, irrespective of their field of specialization in a study 13 .…”
Section: Discussionsupporting
confidence: 92%
“…One study even reported a higher knowledge score among non health care workers than the health care workers 16 . Interestingly, as reported in a study in Cambodia, 17 , primary school students had similar knowledge pattern as that observed for older populations like college students and adults reported in the other studies 5,12,15,18 .…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Our results were consistent with, a study conducted in Karachi which showed that only 8.3% medical students had poor knowledge while 63.2% had good knowledge and 28.3% moderate knowledge (8,9).…”
Section: Discussion:-supporting
confidence: 92%
“…The level of knowledge improved with the term, which is similar to our study. 4 In the Karachi study 7.7% students had excellent knowledge about first aid, in our study that was 28.7%. 2 Another study conducted by department of community medicine in BJ Medical College, Ahmedabad on awareness regarding first aid and fire safety among the second year undergraduate medical students stated that knowledge regarding first aid among the medical student was 33.6%, whereas in our study it was 56.7%.…”
Section: Discussionmentioning
confidence: 82%